PEMAHAMAN PENDIDIKAN KARAKTER BANGSA DENGAN MODEL PEMBELAJARAN KONTEKSTUAL PADA MAHASISWA UNIVERSITAS MUSLIM NUSANTARA (UMN) AL-WASHLIYAH MEDAN - Beta Rapita Silalahi; Eryanti Lisma (Yayasan Akrab Pekanbaru, 2018)
This study aims to examine the understanding of students of Teachers Education of Early Childhood Education (PG-PAUD) Muslim University of Nusantara (UMN) Al-Washliyah Medan on the values of nation character through contextual learning model so that students can apply it in daily life, nation, and state.Learning by using contextual learning model can improve student achievement of Muslim Nusantara University (UMN) Al-Washliyah Medan Prodi PG-PAUD semester VII (seven) B, seen from the improvement of student learning outcomes. Students can understand the character education of the nation by using contextual learning model seen from the increase of the value of the character of the nation by using paired t test on SPSS 20 for windows, the average value increased from 76.36 to 86.82 with t value of -8.521 with sig (2 tailed) 0.000, it shows that the value of contextual learning in cycle 2 is better than cycle 1. Contextual learning and understanding of the character of the nation have a positive effect on student achievement of Universitas Muslim Nusantara University (UMN) Al-Washliyah Medan Prodi PG- PAUD semester VII (seven) B, can be seen from the increasing value of understanding the character of the nation. The result of cycle 2 is better than cycle 1 with the average value increased from 76.36 to 86.82 with t value of -8.521 with sig (2 tailed) 0,000. Keywords: Nation Character, Contextual, PG-PAUD